(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
Digital transformation in public services has become a necessity in improving efficiency, transparency, and accessibility for the community. This study aims to analyze the implementation of the Dukcapil Go Digital program in enhancing the quality of population administration services in Makassar City, focusing on target group behavior and interactions among policy actors. This research employs a qualitative approach with a descriptive method, where data are collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that the implementation of Dukcapil Go Digital has positively contributed to improving service quality, as reflected in the high level of public satisfaction index. However, there are dynamic patterns in target group behavior influenced by digital literacy and access to technology, resulting in unequal ability among citizens to optimally utilize digital services. Furthermore, interactions among policy actors are still dominated by one-way communication, leading to limited public understanding and minimal feedback as a basis for policy evaluation. The decline in the number of website service users in recent years also suggests challenges in maintaining the sustainability of digital service utilization. This study concludes that the success of digital policy implementation is not solely determined by technological aspects, but also by the government’s ability to adopt inclusive, participatory, and adaptive approaches to community characteristics. Therefore, strengthening digital literacy, optimizing two-way communication, and fostering cross-sector collaboration are essential to ensure the effectiveness and sustainability of digital-based public services. Keywords: policy implementation; digital public services; Dukcapil Go Digital; target group behavior; policy actor interaction